Development of Problem Based Learning Physics Teaching Modules to Improve the Argumentation Skills of Students at SMA Negeri 2 Makassar - Oktaviana Beferly Mapau; Jasruddin Daud Malago; Kaharuddin Arafah (Postgraduate, University of Mataram, 2025)
This research is a type of Research and Development (R&D) research with a 4D model development method. The 4D stages include: defining, designing, developing, and disseminating. This research and development aim to design and analyze a physics teaching module based on Problem Based Learning that is valid, practical, and effective and can improve students' argumentation skills. The number of validators who provided an assessment of the validity of the module content was 3 validators, the number of teachers who provided an assessment of practicality was 10 physics teachers, and the physics teaching module based on Problem Based Learning that had been developed was tested on 36 students of class X.9 of SMA Negeri 2 Makassar. The instruments used in this study included validation of the open physics module, teacher response questionnaires, and validated argumentation ability tests. The results of the study indicate that the physics teaching module based on Problem Based Learning is in the valid category with an average Aiken's V value of 0.79, practicality with a percentage of teacher responses of 89% is in the very practical category, and effectiveness with an average N-Gain of 0.62 is in the moderate category. Based on these results, the physics teaching module based on Problem Based Learning as a whole is considered valid, very practical, and quite effective for use in the physics learning process.